Influências da mineração de ouro e ferro nos ecossistemas florestais da área de Serra do Navio e Pedra Branca do Amaparí-AP - MARTINS, Rodrigo e Silva (2019)
This study evaluates the potential environmental assaults committed by mining companies operating in the state of Amapa, in the municipalities of Serra do Navio and Pedra Branca do Amapari, in 2007. Based on a technical report requested by the Office of the State of Amapá (MPEA), through a contract signed with Prof.. Milton Matta (FAGEO-IG-UFPA). The main objective was to assess the degree of aggression on forest ecosystems in areas where existing companies that carry out mining activities are working. The influences on the vegetation in aquatic systems have shown marked only in the areas of river William basin. Especially in the stretch that extends between the river and Amapari gold mine ( MPBA). In other water courses of the studied area, including the streams Silvestre, Mario Cruz and Taboca, the aggression in relation to vegetation are restricted to areas of deforestation for mining activities and the areas of road construction for the various access roads from mining. Some interferences of the MPBA mining company on local vegetation are clear in the studied area, such as discoloration of the water in streams due to the large amount of sediment carried to these ecosystems, which ultimately affects the vegetation can be found there. The main recommendations include the recovery of degraded areas, with creation of the emerging complexity of ecosystems that can restore the cyclical processes. It is suggested to start from Monodominant Ecosystems (eg, grass field), progressing to heterogeneous (mixed) in order achieve maximum structural and functional complexity, both in areas of extraction (removal) and in disturbed areas (industrial infrastructure, support and transportation system.